2001
DOI: 10.1002/1099-0690(200104)2001:7<1323::aid-ejoc1323>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rate Constants for the Reaction of Aryl Radicals with Enolate Ions

Abstract: The rate of ring closure (k C ) of o-(ω-alkenyl)aryl radicals by means of an intramolecular attack of the intermediate phenyl-type radical at the tethered double bond was found to be 4.2 × 10 8 s −1 (for 1 • ) and 7.6×10 7 s −1 (for 8 • ), both being 6-exo-trig processes, and 9.6 × 10 9 s −1 for the 5-exo-trig process of 3 • . The k C rate constant of these radicals was calibrated with respect to a known rate of H-atom abstraction (k H ). The photostimulated S RN 1 reactions of radical clock precursor 1 with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 27 publications
4
86
0
Order By: Relevance
“…[10,11] We have investigated both aryl and vinyl radical intermediates in the past few years, and met with difficulty in locating these kinetic data in an investigation intended to provide rate constant values (k Y ) for reactions between phenyl radical and a series of nucleophiles (Y Ϫ ) (the S RN 1 reaction). [12] To ascertain these k Y values, we needed to know the rate constant of a competing reaction (Scheme 1). Strangely enough, not many kinetic data could be found for a reaction as simple as H-atom abstraction (k H ) by phenyl radical from common H-donor solvents.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…[10,11] We have investigated both aryl and vinyl radical intermediates in the past few years, and met with difficulty in locating these kinetic data in an investigation intended to provide rate constant values (k Y ) for reactions between phenyl radical and a series of nucleophiles (Y Ϫ ) (the S RN 1 reaction). [12] To ascertain these k Y values, we needed to know the rate constant of a competing reaction (Scheme 1). Strangely enough, not many kinetic data could be found for a reaction as simple as H-atom abstraction (k H ) by phenyl radical from common H-donor solvents.…”
Section: Introductionmentioning
confidence: 80%
“…In a previous investigation, [12] o-(but-3-enyloxy)iodobenzene (1) had been employed as a radical clock, and a 4.2·10 8 s Ϫ1 intramolecular rate constant for the involved phenyltype intermediate 1 · (k C in Scheme 2) was obtained at 25°C , [13Ϫ15] by calibration with respect to H abstraction (k H ) from Bu 3 SnH in benzene solution. [15] This k C value was now exploited in turn for the determination of the k H values for two H-donating solvents: Me 2 SO and CH 3 CN.…”
Section: Determination Of H-abstraction Rates With Phenyl-type Radicamentioning
confidence: 98%
“…Given the discouraging results obtained in the reactions of carbanions of ketones with 1-(but-3-enyloxy)-2-iodobenzene in DMSO, 12 we undertook the study of the photostimulated reactions of nitromethane anions in liquid ammonia as solvent. It is known that the enolate anion of acetone does not react with primary alkyl radicals and that nitromethane anion does not initiate S RN 1 reactions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that under the reactions conditions the anions behave as bases and not as nucleophiles; the enolate takes an allylic proton promoting the elimination of 1,3-butadiene as a neutral fragment and 2-iodophenoxide ion as the leaving group. 12 Chromenes and chromanes are widely disseminated in natural product chemistry, and it has been shown that many compounds containing this nucleus have a potent biological activity. 15,16 Antioxidant derivatives of chromenes, which are added to many foodstuffs, pharmaceuticals, and cosmetics to prevent them from becoming rancid, are the object of intensive research efforts.…”
mentioning
confidence: 99%
“…[1][2][3][4] Cyclization of o- (3-butenyl)phenyl radical 2r (kcy = 5 x 10 8 s -1 , 30 °C) to 1-methylindanyl radical 3r and related rearrangements have been used to detect radical intermediates in several reactions. [5][6][7][8] However, cyclization of the o- (3-butenyl)phenyl anion 2c has to be considered (Scheme 1). The reaction of 1 with 2 equiv of n-BuLi yields 42% of cyclization product after 5 minutes at room temperature.…”
Section: Introductionmentioning
confidence: 99%